Advances in mass spectrometry driven O-glycoproteomics - Levery, Steven B.; Steentoft, Catharina; Halim, Adnan; Narimatsu, Yoshiki; Clausen, Henrik; Vakhrushev, Sergey Y. (Biochimica et biophysica acta, 2015)
Global analyses of proteins and their modifications by mass spectrometry are essential tools in cell biology and biomedical research. Analyses of glycoproteins represent particular challenges and we are only at the beginnings of the glycoproteomic era. Some of the challenges have been overcome with N-glycoproteins and proteome-wide analysis of N-glycosylation sites is accomplishable today but only by sacrificing information of structures at individual glycosites. More recently advances in analysis of O-glycoproteins have been made and proteome-wide analysis of O-glycosylation sites is becoming available as well. Here we discuss the challenges of analysis of O-glycans and new O-glycoproteomics strategies focusing on O-GalNAc and O-Man glycoproteomes. A variety of strategies are now available for proteome-wide analysis of O-glycosylation sites enabling functional studies. However, further developments are still needed for complete analysis of glycan structures at individual sites for both N- and O-glycoproteomics strategies. The advances in O-glycoproteomics have led to identification of new biological functions of O-glycosylation and a new understanding of the importance of where O-glycans are positioned on proteins. •What makes O-glycoproteomics particularly challenging?•ETD MS/MS based approaches had provided one solution.•Enrichment protocols for glycopeptides are essential for deep O-glycoproteomics.•Precise gene editing strategies complement functional glycoproteomics.